Ordered to die a history of the Ottoman army in the First World War - Erickson, Edward J. (Contributions in military studies, 2001)
The first general history in English of the Ottoman Army in the First World War, Ordered to Die is based on newly available Turkish archival and official sources. Outnumbered and outgunned, the Ottoman Army performed astonishingly well in the field and managed to keep fighting until the end of the war, long after many other armies had quit the field. It fought a multi-front war against sophisticated and capable enemies, including Great Britain, France, and Russia. Erickson challenges conventional thinking about Ottoman war aims, Ottoman military effectiveness, and the influence of German assis.